A study of the socio-psychological climate of football players at the stage of preliminary basic training - Goncharenko Vladislav (Слобожанський науково-спортивний вісник, 2019)
Purpose: to study the characteristics of the socio-psychological climate of athletes involved in football at the stage of preliminary basic training. Material and methods: analysis of scientific and methodological literature, the methodology "Sociometry" by J. Moreno. Studies were conducted among athletes aged 12-13 years in the amount of 14 people who play football at the stage of preliminary basic training. Results: theoretically proved the need to find new ways of effective interpersonal interaction in a team of football players at the stage of preliminary basic training. Conclusions: a study of the sociometric status of the players showed that the team has two distinct leaders around which the team is forming. It is worth noting that outsiders and completely isolated players and the rest of the team do not want to interact with them to achieve a result. Guidelines for coaches have been developed with the goal of creating a “favorable” socio-psychological climate in the team of football players at the stage of preliminary basic training.